2012
DOI: 10.1007/s00394-012-0466-6
|View full text |Cite
|
Sign up to set email alerts
|

Aspalathin improves hyperglycemia and glucose intolerance in obese diabetic ob/ob mice

Abstract: Hypoglycemic effect of aspalathin is related to increased GLUT4 translocation to plasma membrane via AMPK activation. In addition, aspalathin reduces the gene expression of hepatic enzymes related to glucose production and lipogenesis. These results strongly suggest that aspalathin has anti-diabetic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
119
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(131 citation statements)
references
References 45 publications
12
119
0
Order By: Relevance
“…In a previous study conducted in our laboratory, we confirmed the hypoglycemic activity of an aspalathin-enriched green rooibos extract in vitro and in vivo (Muller et al 2012). In a recent study, Son et al (2012) reported that aspalathin increased glucose uptake in L6 myotubes and activated AMPK phosphorylation thereby increasing GLUT4 translocation to the membrane. AMPK is a major regulator of cellular energy homeostasis and a pharmacological target for anti-diabetic agents such as metformin (Sajan et al 2010).…”
Section: Introductionsupporting
confidence: 86%
“…In a previous study conducted in our laboratory, we confirmed the hypoglycemic activity of an aspalathin-enriched green rooibos extract in vitro and in vivo (Muller et al 2012). In a recent study, Son et al (2012) reported that aspalathin increased glucose uptake in L6 myotubes and activated AMPK phosphorylation thereby increasing GLUT4 translocation to the membrane. AMPK is a major regulator of cellular energy homeostasis and a pharmacological target for anti-diabetic agents such as metformin (Sajan et al 2010).…”
Section: Introductionsupporting
confidence: 86%
“…reported that Asp increased glucose uptake in a skeletal musclederived cell line (Kawano et al, 2009, Son et al, 2013, we investigated whether this mechanism, through GRE-and Aspenhanced glucose utilization in tissues such as skeletal muscle, contributed to the suppressive effects on elevated blood glucose levels in the present study. Particularly, we performed IPGTT using GRE and Asp.…”
Section: Effects Of Gre and Asp On Ipgtt Since It Was Previouslymentioning
confidence: 91%
“…In particular, aspalathin (Asp), a major flavonoid in rooibos, is present at twice the level in unfermented compared to fermented tea (Bramati et al, 2002, Bramati et al, 2003. Asp is a dihydrochalcone-C-glucoside and has been reported to ameliorate hyperglycemia (Kawano et al, 2009, Muller et al, 2012, Son et al, 2013. Therefore, unfermented rooibos tea containing high levels of Asp is of great interest as a food material to promote human health.…”
Section: Rooibos (Aspalathus Linearis) Is a Leguminous Shrub Native Tomentioning
confidence: 99%
See 1 more Smart Citation
“…A study showed that hypoglycemic effect of aspalathin is related to increased GLUT4 translocation to plasma membrane via AMP-activated protein kinase activation. In addition, aspalathin reduces the gene expression of hepatic enzymes related to gluconeogenesis and lipogenesis [32]. Furthermore chalcone derivatives have insulin mimetic properties [2].…”
Section: Discussionmentioning
confidence: 99%